Nonlinear control of electromechanical objects with variable parameters; Russian electrical engineering; Vol. 69, № 10 - Afanas'ev V. N. (1998, 1998)
Nonlinear control of an electromechanical object (EMO) with pulsewidth modulation of the supply voltage to the actuating drive is considered. The use of a nonlinear regulator permits more effective solution of EMO control problems such as maximizing the dynamic accuracy of control and minimizing the losses. The adaptive properties of the nonlinear regulator are established.